Night & day [large type] - Connolly, John, 1968- (Connolly, John, 1968- Nocturnes, 2025)
"Night and Day takes us from the dusty shelves of an uncanny library filled with fictional characters to a bunker deep beneath the earth where scientists seek revenge on old Nazis; from an English marsh haunted by a mother and her son to a country house where a grieving widower finds comfort from a most unlikely source. Concluding with the author's account of how an obscure horror film brought him closer to his lost father, and how nostalgia can help to keep us sane, this is a collection that will move, entertain, and keep you reading late into the night."--